Pengaruh Self Service Technology, Service Quality, Dan Digital Marketing Terhadap Kepuasan Shopeefood (Studi Pada Mahasiswa FEB Unisma Angkatan 2019) - Rochmatul Rochmatul; Muhammad Mansur; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract  The purpose of this study was to determine the effectiveness of self-service techniques and the quality of service and digital marketing on Shopee Food customer satisfaction. The data used in this study were distributing questionnaires to participants and using primary and secondary data to determine the number of active business students in the department. The population of this survey consisted of undergraduate students at the Faculty of Economics, Islamic University of Malang class of 2019, but the sample for this survey consisted of 95 people with certain criteria. The analytical method used in this study is multiple linear analysis using F-tests and t-tests to test hypotheses. Research also shows that shopeefood has a significant effect on customer satisfaction. In part, self-service technology, service quality, and digital marketing have a significant impact on Shopee Food customer satisfaction. Keywords: Self Service Technology, Service Quality And Digital Marketing